Managed services for timely corrective maintenance in ABC Bank - Aquino, Ma. Kathleen S. (Animo Repository, 2023)
In this pandemic period, a pleasant physical work environment contributes to the overall well-being of employees which enhances their efficiency and quality performance. Essential to delivering a high-level convenience to in-store clients is ensuring that all equipment are in good working condition and safe to use by our clients and employees. There should be no grounding issues, electrical shocks, power surges and lighting problems for our clients to feel safe and enjoy their visits to our bank branches. This will prevent any delay in processing the requested financial services of our clients. This action research addressed the issue of delayed completion of corrective equipment maintenance service requests in ABC Unibank. Although equipment maintenance /technical services are not a core function of our Company, ABC bank, they serve as critical back-office support. Our bank needs to establish a well-maintained equipment maintenance system to resolve the issue of delayed resolution of service requests for various equipment. This two-cycle action research therefore aimed to improve the timeliness of resolving service requests for equipment in the bank’s branches to contribute to the pleasant store experience target of the Retail Banking Group (RBG) which also supports employee wellness. Our team used the Maintenance Management Framework to examine current equipment maintenance set-up and determine areas for improvement. The results of this action research benefitted our Company with the reduction in the volume of Corrective Maintenance Services Requests of our bank sites nationwide. This helped our ABC Bank create a well-maintained facility for our employees and clients to conduct business comfortably. Keywords: managed services, preventive maintenance, corrective maintenance, supply chain management, physical work environment, store experience, service requests